Sensitivity of Parasitological Tests in Imported Plasmodium vivax Malaria in Adults and Impact of Chemoprophylaxis and Attack Type. Issue 3 (14th March 2014) - Larréché, Sébastien; Rapp, Christophe; Delacour, Hervé; Sanmartin, Nancy; Ficko, Cécile; Bigaillon, Christine; Andriamanantena, Dina; Pilo, Jean‐Etienne; Mérens, Audrey
<x xml:space="preserve">Abstract</x> Background Plasmodium vivax is the second most common species among cases of imported malaria diagnosed in Europe. The objective of this study is to describe the sensitivity of the parasitological tests in imported P. vivax malaria, and the impact of chemoprophylaxis and attack type (primary infection or relapse). Methods A retrospective study included the imported vivax malaria cases admitted in a French military hospital between 2001 and 2013. The reference diagnosis method was microscopy corrected by polymerase chain reaction (PCR). Thin and thick blood films examination, quantitative buffy coat (QBC) test, and a rapid diagnostic test (RDT) had been systematically performed. PCR had been carried out for ambiguous profiles. Results Eighty‐nine cases recorded from 78 patients were included, 65 of them having recently traveled to French Guyana. Forty‐two patients had properly followed chemoprophylaxis. Forty‐six cases were primary infections while 43 were relapses. The sensitivity was 91% for the thin blood smear, 96% for the concentration techniques (Giemsa thick blood smear and QBC test), and 76% for the RDT. The combination of the three conventional tools has an imperfect sensitivity, both for the positive diagnosis of malaria (96%) and for the diagnosis of vivax species (80%). In 4% of the cases, the positive diagnosis was established only by the PCR. The species identification was established in 20% by the PCR. The sensibility of thin blood smear and of RDT decreased significantly with full compliance of chemoprophylaxis or primary infection, whereas the decrease of sensibility of concentration techniques was not significant. Conclusions This study illustrates the difficulties encountered in vivax malaria diagnosis, especially in patients who properly followed chemoprophylaxis or with primary infection due to a lower parasitemia. It underlines the lack of sensitivity of RDT for P. vivax and emphasizes the need for systematically combining various diagnosis methods.